2016
DOI: 10.3747/co.23.2839
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HLA-DRB1 Allele Polymorphisms and Familial Aggregations of Hepatocellular Carcinoma

Abstract: Objective We explored the relationship between HLA-DRB1 allele polymorphisms and familial aggregation of hepatocellular carcinoma (fhcc).Methods Polymerase chain reaction sequence-specific primers were used to determine HLA-DRB1 genotypes for 130 members of families with 2 or more liver cancer patients and for 130 members of families without any diagnosed cancers. The genotype profiles were then compared to explore the relationship between HLA-DRB1 gene polymorphism and fhcc.Result Of 11 selected alleles, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, familial aggregation and co-aggregation of HCC have indicated that genetic factors play a major role in the development of HCC. Previous molecular studies have reported that genetic factors, such as the genes coding for human leukocyte antigen (HLA)-DRB1, FasL, epidermal growth factor, human serum antigen-miR-1269, cyclooxygenase-2, and methylene tetrahydrofolate reductase, play an essential role in HCC susceptibility (Shen et al, 2015;Wang et al, 2015;Xiong et al, 2015;Zhang et al, 2015;Khalifa et al, 2016;Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, familial aggregation and co-aggregation of HCC have indicated that genetic factors play a major role in the development of HCC. Previous molecular studies have reported that genetic factors, such as the genes coding for human leukocyte antigen (HLA)-DRB1, FasL, epidermal growth factor, human serum antigen-miR-1269, cyclooxygenase-2, and methylene tetrahydrofolate reductase, play an essential role in HCC susceptibility (Shen et al, 2015;Wang et al, 2015;Xiong et al, 2015;Zhang et al, 2015;Khalifa et al, 2016;Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using the BioDrop µLITE, DNA was quantified and purity was verified. Amplification of HLA-DRB1*11 and HLA-DRB1*12 alleles was performed using the primers described by Ma et al [ 27 ], with a slightly adapted amplification program. This was a multiplex PCR targeting both alleles simultaneously, performed with the GeneAmp PCR System 9700 (Applied Biosystem, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis still identified HLA-DRB 1 *12:02 as the top susceptible HLA allele associated with acute-on-chronic liver failure (ACLF) [35]. A large number of studies have been conducted to identify HLA-DRB1 genetic variants associated with HCC risk and clinical outcomes, but many of the findings in these studies are inconsistent and inconclusive [36][37][38]. A meta-analysis by Lin et al reported an ethnicity-dependent association between specific HLA-DRB1 alleles and HCC risk, DRB 1 *07 and DRB 1 *12 were significantly associated with the risk of HCC in the whole populations, and DRB 1 *15 allele significantly increased the risk of hepatocellular carcinoma only in Asians [36].…”
Section: Hla Class II Allele Polymorphism and Hbv Infection Outcomesmentioning
confidence: 99%
“…One research by Ma et al suggests that if genetic factors play a role in familial aggregation of hepatocellular carcinoma, the deficiency in the DRB 1 *11 and DRB 1 *12 alleles might be the risk factor at work in the Guangxi Zhuang Autonomous Region, P.R.C. [37]. Another meta-analysis by Liu et al reported that HLA-DRB 1 *01 and 11 alleles were protective factors, while HLA-DRB 1 *12 and 14 alleles were risk factors for HCC development [38].…”
Section: Hla Class II Allele Polymorphism and Hbv Infection Outcomesmentioning
confidence: 99%